PENGEMBANGAN WISATA MELALUI PEMBERDAYAAN MASYARAKAT (POKDARWIS) DI KELURAHAN SUMBER REJO KECAMATAN BALIKPAPAN TENGAH - Hadiyatno, Didik; Juwari, Juwari; Anam, Hairul (Fakultas Ekonomi Universitas Balikpapan, 2024)
Sumber Rejo Village has variants of potential tourist attractions such as the natural environment which is used as an educational tourism managed by the community with the nickname Kang Bejo, namely the kale village in Sumber Rejo Village, the cultural life of the community is full of values, norms, and customs, so that it makes Sumber Rejo Village worthy of being an important part of tourism activities, especially in the city of Balikpapan. Tourists prefer their friendly visits to nature and local people such as farming, farming and gardening, in the hope of improving cleanliness, accommodation, safety, and comfort. The change in the motivation of tourists who pay more attention to health aspects, prefer cleanliness, accommodation quality, maximum security, and increased comfort is very much in line with the conditions of tourist villages. Tourism villages consistently offer unique and interesting experiences, natural beauty and the nobility of the culture of their people which are depicted through hospitality, politeness, cleanliness, security, and comfort.